PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI IDX30 PERIODE 2012-2016 - Syofria Meidona (IAIN Batusangkar, 2019)
The purpose of this study is to determine the influence of corporate social responsibility disclosure and profitability on firm value in the IDX30 from 2012 until 2016. Sampel in this study amounted to 14 companies by using purposive sampling technique. The data analysis method was the multiple regresian analysis using the spss 16 program. The research result in hypothesis testing with a level og significance 5% (0,05) found that partially corporate social responsibility disclousure hasn’t significant influence on the firm value, because a level of significant 0,559 more than 0,05. While profitability has significant influence on the firm value with a significance value 0,000 < 0,05. Simultaneously corporate social responsibility disclosure and profitability has significant influence on the firm value with a significance value 0,000 < 0,05. The adjusted R2 value 0f 0,749 means that all independent variables ( corporate social responsibility disclosure and profitability) contribute 74,9% in explaining the dependent variable (firm value) and the remaining 25,1% is explained by the outside of this research variable.